Characteristics of hypoglycaemic episodes in diabetic patients treated at the emergency room of a Portuguese tertiary centre, 2012‐2016. Issue 3 (24th May 2020) - Pereira, Catarina A.; Almeida, Raquel; Dores, Jorge
Abstract: Objective: To analyse changes in the characteristics of hypoglycaemic episodes treated in the emergency room of a tertiary hospital in Portugal between 2012 and 2016. Research Design and Methods: We retrospectively analysed all emergency room reports for patients discharged with a diagnosis of hypoglycaemia between 2012 and 2016 and analysed demographic characteristics, type of diabetes and treatments, causes of hypoglycaemia and discharge destination. Patients without diabetes were excluded. Results: In total, 676 hypoglycaemic episodes were analysed. Most patients were female (59%) and the median age of the patients was 71 years (interquartile range, 57‐81). The proportion of hypoglycaemic episodes relative to all emergency episodes decreased from 1.5% in 2012 to 1.0% in 2016 ( P  < .001). The proportion of patients with type 1 diabetes increased from 15.6% to 23.8%, while that of patients with type 2 diabetes decreased from 80.3% to 72.3% (nonsignificant differences). There was an increase in the use of insulin (67.1% to 85.4%, P  = .02) and a decrease in the use of insulin secretagogues (26.6% to 11.5%, P  = .03) over the study period. The rate of hospitalization dropped significantly from 11% in 2012 to 4.3% in 2015 and 5.4% in 2016 ( P  = .02). Conclusions: Despite the increasing use of newer diabetes medications associated with a lower risk of hypoglycaemia, these episodes still require emergency care. The proportion of patients receiving insulin increased over the years, probably due to the slight increase in the prevalence of type 1 diabetes and the increasing replacement of secretagogues with insulin in type 2 diabetes. Abstract : We present the changes in the characteristics of hypoglycaemic episodes treated in the emergency room of a tertiary hospital in Portugal between 2012 and 2016. With the analysis of 676 hypoglycaemic episodes, we can better understand and reflect on the reasons why, despite the increasing use of newer diabetes medications associated with a lower risk of hypoglycaemia, these episodes still require emergency care.